TACE combined with regorafenib with or without anti-PD-1 therapy for advanced HCC after targeted therapy failure: a multicenter real-world study - Li, Yan; Yuan, Hang; Yao, Quan-Jun; Geng, Xiang; Xu, Fei; Fan, Weijun; Wu, Gang; Cao, Guang-Shao; Song, Ho-Young; Hu, Hong-Tao (Frontiers in Oncology, 2025)
Background and objectivesPatients with hepatocellular carcinoma (HCC) progressing after targeted therapy face limited treatment options and poor prognosis. Although regorafenib is an established second-line therapy, its combination with locoregional and immunotherapeutic approaches remains insufficiently characterized in real-world settings. This multicenter study evaluated the efficacy and safety of combining transarterial chemoembolization (TACE) with regorafenib and anti-PD-1 therapy in advanced HCC (BCLC B/C) after targeted therapy failure, with a focus on optimizing treatment timing and dosing strategies.MethodsWe conducted a retrospective, multicenter, propensity score-matched study involving 188 HCC patients from five tertiary medical centers between June 2022 and June 2024. Among them, 103 patients received triple therapy (TRP group: TACE combined with regorafenib and PD-1 inhibitors), while 85 received dual therapy (TR group: TACE combined with regorafenib). After propensity score matching (PSM), 64 patients were included in each group. Primary endpoints included progression-free survival (PFS) and overall survival (OS), evaluated per mRECIST v1.1 criteria, with secondary endpoints including objective response rate (ORR), disease control rate (DCR), and treatment-related adverse events (TRAEs). Subgroup analyses examined the effects of regorafenib initiation timing (second-line versus third-line or later) and dosage (80 mg vs 120–160 mg) on PFS.ResultsThe triple therapy group demonstrated significantly superior efficacy compared to the dual therapy group. After PSM, the TRP group showed significantly improved median PFS (6.5 vs. 4.6 months) and OS (15.8 vs. 12.1 months), along with significantly higher ORR (32.8% vs. 17.2%) and DCR (.71.9% vs. 51.6%) compared to the TR group. Earlier regorafenib initiation (second-line) was associated with substantially prolonged PFS in both treatment arms (TRP group: 7.2 vs 5.1 months; TR group: 5.1 vs 4.2 months), whereas dosage variations did not significantly affect survival outcomes. TRAEs were comparable between groups except for a higher incidence of rash in the triple therapy group (25.0% vs 6.3%).ConclusionsThe triple combination of TACE, regorafenib, and PD-1 inhibitors demonstrated superior clinical efficacy compared with TACE-regorafenib dual therapy in advanced HCC patients after targeted therapy failure, with optimal outcomes observed following earlier regorafenib initiation and an acceptable safety profile.